The efficacy of a brief hazard perception interventional program for child bicyclists to improve perceptive standards. (August 2018) - Zeuwts, Linus H.R.H.; Cardon, Greet; Deconinck, Frederik J.A.; Lenoir, Matthieu
Highlights: Evaluating a brief hazard perception intervention in child bicyclists. Child bicyclists were compared to adult bicyclists. Children improved response rate and reaction times, but not visual behaviour. The training was too short to improve children towards the level of adults. Abstract: Introduction: Even though child bicyclists are highly vulnerable in traffic only few studies focused on providing child bicyclists with means to enhance their abilities to deal with the complexity of dynamic traffic situations. The current study therefore evaluated whether a brief hazard perception intervention might be effective to improve hazard perception skills in child bicyclists towards a level more comparable to adult bicyclists. Methods: Eighty children of the fourth grade (9.03 ± 0.43 years; 34 girls) and forty-six adults (34.67 ± 14.25 years age; 24 woman) first performed a Hazard Perception test for bicyclists. Response rate, reaction times, first fixation, duration of the first fixation, dwell time and total number of fixations on the events were measured. Next, the children took part in the HP intervention in which video clips of dangerous traffic situations were presented. The intervention comprised two classroom sessions of one hour (1/week). A post-test was performed one day after and the retention-test three weeks after the intervention. Results: Children responded to more covert hazards immediately after the intervention (p < 0.05), but did not improve their response rate for overt hazards. Reaction times for the covert hazards improved on the post-test (p < 0.001) compared to the pre-test but this effect was reduced on the retention test. There was no effect of the intervention for entry time of the first fixation but the duration of the first fixation increased for the covert hazards (p < 0.05). Children made fewer fixations on the event compared to adults (p < 0.001), except for the covert hazards on the retention-test. The training also increased the number of fixations for the overt hazards on the post-test (p < 0.001) and the retention-test (p < 0.001) but only increased on the retention test for the covert hazards (p < 0.001). Conclusion: The results demonstrated that a brief intervention for training hazard perception skills in child bicyclists is able to improve children's situation awareness and hazard perception for potential dangerous situations. The training, however, was too short to improve children to higher adult levels.